Learning chemistry using 3D approach : 3D atomic cubic - Mohd Hatta, Nuraziera (2014)
This research is about the development of the 3D courseware named as 3D-Atomic Cubic as a tool for teaching and learning Chemistry subject. This 3D-Atomic Cubic courseware contains all multimedia elements used to attract students’ attention for learning the contents. This courseware is specifically developed for a topic in Chemistry subject for student of Mechanical Engineering in Universiti Teknikal Malaysia Melaka (UTeM). The questionnaire is the instrument used in this research to determine the problem statement. Based on the questionnaires, Properties of Matter topic is identify as the most difficult topic, because students need to understand and visualize the arrangement of the atom in Cubic Cell. One of their problems faced when learning this topic is student enable to imagine the arrangement of the atom easily. By using traditional approach, the visualization of the model is using two dimensional (2D) models, as a result student hard to imagine the real scenario. This research is focusing on delivery approach of learning by using three dimensional (3D) approaches in studying Chemistry subject. The advantages gained from this research can benefit the students, lecturers, education industry, high institution and also the public. The development methodology of 3D Atomic Cubic courseware was developed using life cycle of 3D Atomic Cubic that based on the ADDIE model. This methodology consist five phase represents a series of task that help to ensure the development efforts stay on tract, on time and on target. Completing each phase is an important element for the instructional design process. For the preliminary analysis, 52 students from the whole Mechanical Engineering students who already took Chemistry subject are involved in determining the difficult topic in Chemistry subject. For evaluation on the effectiveness of 3D-Atomic Cubic Courseware, 52 of Mechanical Engineering students from UTeM is involved and they are divided by two which are Conventional and Experimental Group. From the analysis of the result, both of conventional and experiment group showed an improvement but the student who use 3D-Atomic Cubic courseware get higher mark. This shows that 3D-Atomic Cubic courseware can be used as teaching aid material in classroom since it shows those students who use the courseware get better result. This research found that a 3D element is very useful in helping students to understand chemistry subject especially in visualizing the arrangement of the atom.